2019
DOI: 10.1016/j.stem.2018.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Organoid-Induced Differentiation of Conventional T Cells from Human Pluripotent Stem Cells

Abstract: Summary The ability to generate T cells from self-renewing pluripotent stem cells (PSC) has the potential to transform the current practice of autologous T cell immunotherapy into universal off-the-shelf products. However, differentiation of human PSCs into mature, conventional T cells has been challenging with existing methods. We report that a 3D artificial thymic organoid (PSC-ATO) system induced efficient differentiation of human embryonic stem cell and induced pluripotent stem cell-derived mesoderm progen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
176
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(178 citation statements)
references
References 52 publications
1
176
0
1
Order By: Relevance
“…OP9-DLL1, OP9-DLL4, and analogs based on the TSt4 cell line made it possible to dissect gene regulatory network circuitry and roles of signaling and transcription factors in T-cell commitment in real time, often at single-cell resolution. Whereas these monolayer systems were inefficient at mimicking the later stages of intrathymic T-cell development, a very recent cell linebased organoid culture system has proven to support more complete T-cell development, albeit at the cost of less proliferation than in OP9-based systems (Seet et al 2017;Montel-Hagen et al 2019). The mechanisms described in this review have been revealed and reinforced through combined use of in vivo and in vitro microenvironments for T-cell development.…”
Section: Background: the Thymic Microenvironmentsmentioning
confidence: 99%
“…OP9-DLL1, OP9-DLL4, and analogs based on the TSt4 cell line made it possible to dissect gene regulatory network circuitry and roles of signaling and transcription factors in T-cell commitment in real time, often at single-cell resolution. Whereas these monolayer systems were inefficient at mimicking the later stages of intrathymic T-cell development, a very recent cell linebased organoid culture system has proven to support more complete T-cell development, albeit at the cost of less proliferation than in OP9-based systems (Seet et al 2017;Montel-Hagen et al 2019). The mechanisms described in this review have been revealed and reinforced through combined use of in vivo and in vitro microenvironments for T-cell development.…”
Section: Background: the Thymic Microenvironmentsmentioning
confidence: 99%
“…A prominent method to generate T cells is an in vitro system via co-culture of either mouse or human hematopoietic stem/ progenitors (HSPCs) with stromal cell lines expressing the Notch ligand, such as OP9-DL1/DL4 or 3D-based MS5-hDLL1/4. [1][2][3] Despite the great contribution of this approach to studying T cell development in vitro, phenotypic T cells produced by this approach face severe immunocompetency problems in vivo after engraftment, due to the inadequate in vitro recapitulation of natural thymus microenvironment. Natural mouse Sca1 + cKit + and human CD34 + blood progenitor cells can be induced into CD7 + pre-thymic cells in vitro, which successfully colonize thymi and mature into immunocompetent T cells in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…The generation of CD8αβ + SP T cells from human pluripotent stem cells without activation-mediated agonist selection has subsequently been demonstrated by the use of 3D murine stromal cell culture 32 . However, physiological positive selection is dependent on the interaction of TCR with self-peptide-MHC complexes, which are uniquely processed and presented by thymic cortical epithelial cells 33 .…”
Section: Discussionmentioning
confidence: 99%